Comparative analysis of the interaction of mono-, dis-, and tris-azo food dyes with egg white lysozyme: A combined spectroscopic and computational simulation approach. (30th June 2019) - Wu, Di; Duan, Ran; Geng, Fang; Hu, Xia; Gan, Na; Li, Hui
Highlights: The mono-, dis- and tris-azo food dyes presented good affinity to bind to lysozyme. Binding was predominantly the result of hydrogen bonds and van der Waals forces. Different association strength led to different degrees of unfolding of lysozyme. Abstract: Egg white lysozyme plays an important role in the processing of high value-added poultry products. Considering its applications in the food industry, lysozyme could interact with other food additives, thereby impacting their performance. The present study comparatively investigated the interaction and orientation of the mono-, dis-, and tris-azo food dyes with egg white lysozyme. Allura red AC, brilliant black PN and direct brown 1 bound to lysozyme through a static quenching mechanism with 10 5 magnitude binding constants. The binding affinity, mainly driven by hydrogen bonds and van der Waals forces, follows the order: direct brown 1 > brilliant black PN > allura red AC. Based on structural and computational analysis, the addition of the monoazo/disazo/trisazo dye led to differing degrees of lysozyme unfolding and numbers of azo groups. The type of substituents on the structures has momentous influence on the transportation and distribution of food dyes to egg white lysozyme.